Impact of Age and Sex on COVID-19 Severity Assessed From Radiologic and Clinical Findings - Statsenko, Yauhen; Al Zahmi, Fatmah; Habuza, Tetiana; Almansoori, Taleb M.; Smetanina, Darya; Simiyu, Gillian Lylian; Neidl-Van Gorkom, Klaus; Ljubisavljevic, Milos; Awawdeh, Rasha; Elshekhali, Hossam; Lee, Martin; Salamin, Nassim; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
Background: Data on the epidemiological characteristics and clinical features of COVID-19 in patients of different age and sex are limited. Existing studies have mainly focused on the pediatric and elderly population. Objective: Assess whether age and sex interact with other risk factors to influence the severity of SARS-CoV-2 infection. Material and methods: The study sample included all consecutive patients who satisfy the inclusion criteria and who were treated from 24 February to 1 July 2020 in Dubai Mediclinic Parkview (560 cases) and Al Ain Hospital (605 cases), United Arab Emirates. We compared disease severity estimated from the radiological findings among patients of different age-groups and sex. To analyze factors associated with an increased risk of the severe disease we applied uni- and multivariate regression analysis. Specifically, age, sex, laboratory findings, and personal risk factors were used to predict moderate and severe COVID-19 with conventional machine learning methods. Results: Need for O2 supplementation was positively correlated with age. Intensive care was required more often for men of all ages (p < 0.01). Males were more likely to have at least moderate disease severity (p = 0.0083). These findings were aligned with the results of biochemical findings, and suggest a direct correlation between older age and male sex with a severe course of the disease. In young males (18-39 years), the percentage of the lung parenchyma covered with consolidation and density characteristics of lesions were higher than other age groups; however, there was no marked sex difference in middle-aged (40-64 years) and older adults ( 65 years). From the univariate analysis, the risk of the non-mild COVID-19 was significantly higher (p < 0.05) in midlife adults and older adults compared to young adults. The multivariate analysis provides similar findings. Conclusion: Age and sex are important predictors of disease severity in the set of data typically collected on admission. Sexual dissimilarities reduce with age. Age disparities are more pronounced if studied with the clinical markers of disease severity than with the radiological markers. The impact of sex on the clinical markers is more evident than of age in our study.